Enhanced Release of Glucose Into the Intraluminal Space of the Intestine Associated With Metformin Treatment as Revealed by [18F]Fluorodeoxyglucose PET-MRI - Morita, Yasuko; Nogami, Munenobu; Sakaguchi, Kazuhiko; Okada, Yuko; Hirota, Yushi; Sugawara, Kenji; Tamori, Yoshikazu; Zeng, Feibi; Murakami, Takamichi; Ogawa, Wataru (Diabetes care, 2020)
Positron emission tomography (PET)-computed tomography has revealed that metformin promotes the intestinal accumulation of [ F]fluorodeoxyglucose (FDG), a nonmetabolizable glucose derivative. It has remained unknown, however, whether this accumulation occurs in the wall or intraluminal space of the intestine. We here addressed this question with the use of [ F]FDG PET-MRI, a recently developed imaging method with increased accuracy of registration and high soft-tissue contrast. Among 244 individuals with type 2 diabetes who underwent PET-MRI, we extracted 24 pairs of subjects matched for age, BMI, and HbA level who were receiving treatment with metformin (metformin group) or were not (control group). We evaluated accumulation of [ F]FDG in different portions of the intestine with both a visual scale and measurement of maximum standardized uptake value (SUV ), and such accumulation within the intestinal wall or lumen was discriminated on the basis of SUV . SUV of the jejunum, ileum, and right or left hemicolon was greater in the metformin group than in the control group. [ F]FDG accumulation in the ileum and right or left hemicolon, as assessed with the visual scale, was also greater in the metformin group. SUV for the intraluminal space of the ileum and right or left hemicolon, but not that for the intestinal wall, was greater in the metformin group than in the control group. Metformin treatment was associated with increased accumulation of [ F]FDG in the intraluminal space of the intestine, suggesting that this drug promotes the transport of glucose from the circulation into stool.